Long-term antibacterial, antioxidative, and bioadhesive hydrogel wound dressing for infected wound healing applications. (31st January 2023) - Dong, Yaning; Li, Youxin; Fan, Birong; Peng, Wan; Qian, Weijian; Ji, Xiaoxue; Gan, Donglin; Liu, Pingsheng
Abstract : QL–PHMB complex was incorporated into the PAM network to fabricate long-term antibacterial, robust adhesive, and antioxidative hydrogel for infected wound healing. Abstract : Bacterial infection and oxidative stress hinder clinical wound healing. Therefore, wound dressings with antibacterial and antioxidative properties are urgently needed. In this study, a type of quaternized lignin (QL) functionalized poly(hexamethylene biguanide) hydrochloride (PHMB) complex incorporated polyacrylamide (QL–PHMB–PAM) hydrogel was developed as a multifunctional dressing material for the promotion of infected wound repair. Owing to the abundant catechol groups of quaternized lignin, the QL–PHMB–PAM hydrogel exhibited robust repeatable adhesiveness to various substrates with antioxidative properties. Additionally, the antibacterial components of PHMB in the QL–PHMB–PAM composite hydrogel showed high efficiency and long-term antibacterial activity against Staphylococcus aureus (S.aureus), Escherichia coli (E.coli), and methicillin-resistant S. aureus ( MRSA ; up to 100%). Furthermore, in vivo experiments indicated that this multifunctional hydrogel accelerated the healing of S. aureus -infected wounds by promoting the reconstruction of blood vessels and hair follicles. These results demonstrate that this antioxidative, antibacterial, and bioadhesive hydrogel is a promising alternative wound dressing material for the prevention of bacterial infections and the acceleration of infected wound regeneration.